Analisis Faktor Penyebab Kecelakaan Kerja Pada Industri Pertambangan (Study Kasus Ledakan Tungku Smelter Pada PT ITSS Dalam PT IMIP) - Naufal Alfaruqi Masyam; Andi Ilham Samanlangi; Moh. Khaidir Noor; Enni Tri Mahyuni; A. Al Faizah Ma'rief; Hedianto .; Tri Utomo Taliding; Aris Munandar (Program Studi Teknik Pertambangan, Fakultas Sains dan Teknik, Universitas Bangka Belitung, 2025)
At that time the melting incident occurred at PT Indonesia Thingshan Stainless Steel (ITSS) at around 17.30 WITA, involving 18 people, consisting of 10 Indonesian employees and 8 foreign employees. From this explosion, 33 other employees also experienced dizziness. The purpose of this study was to determine the factors causing work accidents in the mining industry in this case is to describe the incident that occurred at PT ITSS which is located in PT IMIP. This study used the literature review method, with data from Google Scholar using HIRARC (Hazard Identification, Risk Assessment and Risk Control) analysis. The results of the study showed that of the five factors that most influenced the work accidents that occurred at PT ITSS which is located in PT IMIP were man factors and environmental factors where there was negligence in the use of PPE that did not meet standards so that several people died and foreign workers were found who did not comply with the contract and could not speak Indonesian at all had violated work procedures, communication difficulties, these violations can complicate work coordination. This causes operations not to comply with the protocol, which leads to work accidents.